Epigenetic response of Louisiana Waterthrush Parkesia motacilla to shale gas development. (20th April 2020) - Frantz, Mack W.; Wood, Petra B.; Latta, Steven C.; Welsh, Amy B.
Abstract : Epigenetic mechanisms such as DNA methylation may vary in response to environmental stressors and introduce adaptive or maladaptive gene expression within and among wild bird populations. We examined the association between DNA methylation and demographic characteristics of the Louisiana Waterthrush Parkesia motacilla in territories with and without disturbance from shale gas development in a Central Appalachian watershed during 2013–2015. We also evaluated the degree to which an individual's methylated state was subject to change across years in individuals that returned over the course of more than one breeding season (i.e. recaptures). Overall, population methylation differed between adult male and female Waterthrush where adult males generally had fewer methylated restriction sites. Methylation also differed between adult females and nestlings. Age influenced methylation in both adult males and females with a decrease in methylation with age, although adult female recaptures had increased methylation with age. Adult males were variably methylated between shale gas undisturbed and disturbed areas at a population and restriction site (i.e. loci) level, where restriction sites were predominately less methylated in shale gas‐disturbed areas. Barium (Ba) and strontium (Sr) data from 2013 feather samples showed adult males had fewer methylated sites at higher concentrations of Ba and Sr, whereas nestlings displayed no correlation of methylation to Ba and Sr concentrations. Adult females displayed increased methylation with increased Sr, a trend also seen year to year in adult female recaptures. Overall, results of our study suggest sex‐specific influences of shale gas development on gene expression that may affect long‐term population survival and fitness.